Sediment Transport Modeling at Jelitik Estuary, Sungailiat - Bangka Regency for the Design of Sediment Control Structures. (September 2020) - Wibowo, M; Hendriyono, W; Rahman, R A; Susatijo, G; Kongko, W; Istiyanto, D C; Widagdo, A B; Nugroho, S; Khoirunnisa, H; Wiguna, E; Aziz, H; Santoso, B
Abstract: Since 2014 sedimentation at the estuary of Jelitik river, Sungailiat, Bangka has continued to increase. At this estuary, the ship traffic is very busy and there is National Fisheries Port Sungailiat. When the tide is low, the river mouth closes thus disrupting ship traffic. The Bangka Belitung Provincial Government is currently planning to build a sediment control infrastructure to reduce the sedimentation rate. To plan and determine the effectiveness of the jetties requires knowledge of sedimentation patterns around Jelitik estuary. Therefore this study was conducted to determine the pattern of sedimentation (distribution and rate) at the existing and ultimate conditions. The methods are field survey, analysis of field data, and computational modeling of sediment transport. Modeling of sediment transport was done using the Sand Transport Module of MIKE 21. Two scenarios were simulated for the existing and ultimate conditions. Based on this modeling, the sedimentation rate at Jelitik estuary is found uneven. In the existing condition, a large rate of sedimentation occurs on the southern side of the Jelitik River estuary, which reaches a maximum value of 2.75 m/year, with an average of 4.44 cm/year. Whereas in the ultimate condition, the sedimentation rate decreases to 0.0377 m/year.